2019
DOI: 10.35726/jp.v24i2.365
|View full text |Cite
|
Sign up to set email alerts
|

Total Leukosit Dan Diferensial Leukosit Darah Ayam Kampung Yang Terpapar Ascaridia Galli Secara Alami

Abstract: This study aims to determine the total number of leukocytes and differential leukocytes of native chicken blood exposed to Ascaridia galli naturally. Sampling of free-range chicken blood was carried out in Amarasi Subdistrict of Kupang Regency while blood tests were carried out at the Veterinary UPT Laboratory of the Animal Husbandry Department of NTT Province. The variables observed were blood figures, especially the total number of leukocytes, lymphocytes, monocytes, neutrophils, basophils, and eucinophils. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Lymphocytes are part of the white blood cells in the agranulocyte group. Lymphocytes play a role in response to antigens and stress by increasing antibody circulation [ 31 ]. When antigens enter the body, lymphocytes quickly respond to the immune system by stimulating and eliciting an initial response called the primary immune response [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lymphocytes are part of the white blood cells in the agranulocyte group. Lymphocytes play a role in response to antigens and stress by increasing antibody circulation [ 31 ]. When antigens enter the body, lymphocytes quickly respond to the immune system by stimulating and eliciting an initial response called the primary immune response [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The condition of chickens that are stressed or attacked by disease have a lymphocyte content that tends to increase, this is in response to attacks by disease agents. According to Moenek et al (2019) that the increase in the lymphocyte value and above the normal value can be caused by the response of the chicken body to the incoming antigen (endoparasites, bacteria, or viruses). Bkrisirna et al (2013) stated that lymphocytes play a role in responding to foreign objects by forming antibodies and developing immunity.…”
Section: Resultsmentioning
confidence: 99%
“…The P2 treatment showed the highest lymphocyte value, which indicated that the P2 treatment chickens experienced the most impact due to consuming rubber seeds with HCN content above the safe limit. According to Moenek et al (2019) that lymphocytes play a role in responding to antigens (foreign bodies) by forming antibodies and developing immunity. The normal limit for lymphocytes is 45-70 x 10 3 /µL.…”
Section: Blood Profile Of Native Chicken Fed Fermented Rubber Seedmentioning
confidence: 99%